2010
DOI: 10.1063/1.3447932
|View full text |Cite
|
Sign up to set email alerts
|

ZnO nanoparticle surface acoustic wave UV sensor

Abstract: The response to ultraviolet illumination of ZnO nanoparticles deposited on LiNbO3 substrate was investigated using surface acoustic waves (SAWs) in the wide range of UV wavelengths from 280 to 375 nm. Deposition of ZnO nanoparticles caused a SAW transmission loss of 27 dB at 64 MHz due to the acoustoelectric attenuation. Acoustoelectric change in the SAW velocity by 3.78×10−4 under 375 nm illumination led to downshift in transmitted SAW phase by 5.5° at UV power density of 691 μW/cm2. The spectral measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 18 publications
0
57
0
Order By: Relevance
“…Simple SAW can be used to transport charge carriers in semiconductor quantum well structures fabricated in thin-film GaAs=InGaAs atop LN (Rotter et al, 1999) to even form moving quantum dots as reported by Fletcher et al (2003), naturally leading to the use of such quantum dots in quantum computing by Furuta et al (2004) and even SAW-induced luminescence (Gell et al, 2006) in the quest to obtain a single-photon source. Aside from quantum applications, the ability to transport charge within semiconductors offers interesting applications in UV detectors using epitaxial ZnO thin films (Emanetoglu et al, 2004) and ZnO nanoparticles (Chivukula et al, 2010), and even solar cells (Yakovenko et al, 2009). …”
Section: A Improvement Of Analysis Techniquesmentioning
confidence: 99%
“…Simple SAW can be used to transport charge carriers in semiconductor quantum well structures fabricated in thin-film GaAs=InGaAs atop LN (Rotter et al, 1999) to even form moving quantum dots as reported by Fletcher et al (2003), naturally leading to the use of such quantum dots in quantum computing by Furuta et al (2004) and even SAW-induced luminescence (Gell et al, 2006) in the quest to obtain a single-photon source. Aside from quantum applications, the ability to transport charge within semiconductors offers interesting applications in UV detectors using epitaxial ZnO thin films (Emanetoglu et al, 2004) and ZnO nanoparticles (Chivukula et al, 2010), and even solar cells (Yakovenko et al, 2009). …”
Section: A Improvement Of Analysis Techniquesmentioning
confidence: 99%
“…ZnO is the only semiconductor material extensively investigated after Si/Ge. Robust ZnO has important applications in the field of biosensors, solar cell window, surface acoustic devices, gas sensor, and piezo actuator devices [2,3]. Recently, semiconductor nanoparticles have attracted much attention due to their excellent properties like optical, structural, and magnetic.…”
Section: Introductionmentioning
confidence: 99%
“…Fro m Fig.2, it is obviously that the SAW velocity decreases monotonously with the sheet conductivity of sensing layer increasing and this analytic solution can be used to explain the reported experimental results [10][11][12] appro ximately. In fact, the response of detector is affected by many co mp lex factors, so an accurate simulat ion for the optimization design and the characteristics analysis of detector is very necessary.…”
Section: A the Conductivity Sensitive Theorymentioning
confidence: 73%
“…It is also found that the absorption of the detected material can change not only the mass of the sensing layer but also the sensing layer conductivity. And because of this, a lot of SAW sensors based on the sensing layer conductivity have been reported [8][9][10][11][12]. Therefore, in addition to the added mass, the variation of the sensing layer conductivity must be taken into consideration in the SAW sensor.…”
Section: Introductionmentioning
confidence: 99%